The kindest lie : a novel - Johnson, Nancy (Novelist) (William Morrow, an imprint of HarperCollinsPublishers, 2021)
It's 2008, and the rise of Barack Obama ushers in a new kind of hope. In Chicago, Ruth Tuttle, an Ivy-League educated black engineer, is married to a kind and successful man. He's eager to start a family, but Ruth is uncertain. She has never gotten over the baby she gave birth to, and abandoned, when she was a teenager. She had promised her family she'd never look back, but Ruth knows that to move forward, she must make peace with the past. Returning home, Ruth discovers the Indiana factory town of her youth is plagued by unemployment, racism, and despair. Determined, Ruth begins digging into the past. As she uncovers burning secrets her family desperately wants to hide, she unexpectedly befriends Midnight, a young white boy who is also adrift and looking for connection. When a traumatic incident strains the town's already searing racial tensions, Ruth and Midnight find themselves on a collision course that could upend both their lives.